Heterogeneous Nuclear Ribonucleoprotein E2 (hnRNP E2) Is a Component of TDP-43 Aggregates Specifically in the A and C Pathological Subtypes of Frontotemporal Lobar Degeneration - Kattuah, Wejdan; Rogelj, Boris; King, Andrew; Shaw, Christopher E.; Hortobágyi, Tibor; Troakes, Claire (Frontiers in Neuroscience, 2019)
TAR DNA-binding protein 43 (TDP-43) is the major component of the ubiquitin-positive protein aggregates seen in the majority of frontotemporal lobar degeneration and amyotrophic lateral sclerosis cases. TDP-43 belongs to the heterogeneous nuclear ribonucleoprotein (hnRNP) family that is involved in the regulation of RNA transcription, splicing, transport and translation. There are a great many hnRNPs, which often have overlapping functions and act cooperatively in RNA processing. Here we demonstrate that another hnRNP family member, hnRNP E2, shows a striking accumulation within dystrophic neurites and cytoplasmic inclusions in the frontal cortex and hippocampus of a subset of FTLD-TDP cases belonging to pathological subtypes A and C, where hnRNP E2 was found to co-localize with 87% of TDP-43 immunopositive inclusions. hnRNP E2-positive inclusions were not seen in FTLD-TDP cases with the C9orf72 expansion or in any other neurodegenerative disorders examined. This interaction with TDP-43 in specific FTLD subtypes suggests different underlying neurodegenerative pathways.